2022
DOI: 10.18502/tim.v7i2.9920
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compound Honey Syrup on Clinical Manifestation of the Adult Asthma Patients: A Randomized, Double-Blinded, Placebo-Controlled Clinical Trial

Abstract: Asthma is a chronic inflammatory disease of the respiratory tract which includes inflammation and obstruction of the airways. Modern medical treatment has side effects in addition to therapeutic effects. According to the high incidence of asthma, the use of complementary therapies has risen, such as compound honey syrup in Traditional Persian medicine and Integrative medicine as a treatment for asthma. Therefore, the aim of this study was to evaluate the effect of compound honey syrup in improving the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Different clinical trials recommended the capability of honey in alleviating histopathological changes in allergic asthma and its capacity to prevent asthma development. With further developments, it was also revealed that several factors like night symptoms, shortness of breath and wheezing were significantly decreased in both groups pertaining to adult asthmatic patients [16]. Abbas et al [17] stated that aerosolized honey permits a rapid absorption towards the airways as it ensures its total deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Different clinical trials recommended the capability of honey in alleviating histopathological changes in allergic asthma and its capacity to prevent asthma development. With further developments, it was also revealed that several factors like night symptoms, shortness of breath and wheezing were significantly decreased in both groups pertaining to adult asthmatic patients [16]. Abbas et al [17] stated that aerosolized honey permits a rapid absorption towards the airways as it ensures its total deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In Persian medicine, the treatment of asthma with herbs has been mentioned in various formulas [ 1 ]. Despite the rich variety of medicinal preparations in Persian medicine, there has been limited research on their effectiveness and possible adverse effects [ 2 - 6 ]. Considering the increasing popularity of herbal and traditional remedies, it is necessary to evaluate the performance of these herbal therapeutic formulations and their side effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%